2019
DOI: 10.3390/w11020319
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Dimensional Hydro-Climatic Similarity and Classification Framework Based on Budyko Theory for Continental-Scale Applications in China

Abstract: Our knowledge of the similarities and differences in ecological systems is vital to understanding the co-evolution of ecological factors. This study proposes a multi-dimensional hydro-climatic similarity and classification framework based on Budyko theory. The framework employs the dryness index (DI), evaporative index (EI), and an empirical parameter (ω) to further sub-divide four climatic zones (humid, semi-humid, semi-arid, and arid zones) in terms of DI. A criterion that define the similarities between sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In particular, the idea that the catchment-specific parameter is an effective empirical parameter related to biophysical features (i.e., interpretation 1) has been widely embraced by the catchment hydrology community, which has identified and grouped relevant biophysical features into three categories (Donohue et al, 2012;Harman and Troch, 2014): (1) climate variability, (2) catchment physical processes, and (3) vegetation structure and function. While it is generally well acknowledged that certain climatic variables (e.g., precipitation variability or the fraction of precipitation falling as snow) can influence the catchment-specific parameter (e.g., Roderick and Farquhar, 2011;Berghuijs and Woods, 2016), in practice, many studies effectively neglect this, instead focusing primarily on the role of landscape features or vegetation functioning (C. Zhang et al, 2004Zhang et al, , 2018Yang et al, 2008Yang et al, , 2016Greve et al, 2015;Xu et al, 2013;Donohue et al, 2012;Knighton et al, 2020;Gao et al, 2020;Chen et al, 2020;Wu et al, 2019;Qiu et al, 2019;J. Liu et al, 2019b;Guo et al, 2019).…”
Section: Current Interpretations Of Explicit Budyko Curves and The Pa...mentioning
confidence: 99%
“…In particular, the idea that the catchment-specific parameter is an effective empirical parameter related to biophysical features (i.e., interpretation 1) has been widely embraced by the catchment hydrology community, which has identified and grouped relevant biophysical features into three categories (Donohue et al, 2012;Harman and Troch, 2014): (1) climate variability, (2) catchment physical processes, and (3) vegetation structure and function. While it is generally well acknowledged that certain climatic variables (e.g., precipitation variability or the fraction of precipitation falling as snow) can influence the catchment-specific parameter (e.g., Roderick and Farquhar, 2011;Berghuijs and Woods, 2016), in practice, many studies effectively neglect this, instead focusing primarily on the role of landscape features or vegetation functioning (C. Zhang et al, 2004Zhang et al, , 2018Yang et al, 2008Yang et al, , 2016Greve et al, 2015;Xu et al, 2013;Donohue et al, 2012;Knighton et al, 2020;Gao et al, 2020;Chen et al, 2020;Wu et al, 2019;Qiu et al, 2019;J. Liu et al, 2019b;Guo et al, 2019).…”
Section: Current Interpretations Of Explicit Budyko Curves and The Pa...mentioning
confidence: 99%
“…CC BY 4.0 License. Xiangyu et al, 2020;Song et al, 2020;Sinha et al, 2020;Li et al, 2020d;Li et al, 2020a;Deng et al, 2020;Zhang et al, 2019a;Young et al, 2019;Xin et al, 2019;Wang et al, 2019;Lv et al, 2019;Liu et al, 2019c;Lee and Yeh, 2019;Kazemi et al, 2019;He et al, 2019c;He et al, 2019b;He et al, 2019a;Wang et al, 2018;Xu et al, 2014). We argue and demonstrate herein that the two widely accepted parametric Budyko equations are non-unique, meaning they are only two of many possible single-parameter Budyko equations.…”
Section: Introductionmentioning
confidence: 59%
“…(2) catchment physical processes; and (3) vegetation structure and function. While it is generally well acknowledged that certain climatic variables (e.g., rainfall variability or the fraction of precipitation falling as snow) can influence the catchment-specific parameter (e.g., (Roderick and Farquhar, 2011;Berghuijs and Woods, 2016)), in practice, many studies effectively neglect this, instead focusing primarily on the role of landscape features or vegetation functioning (Wang et al, 2016a;Zhang et al, 2018;Yang et al, 2016;Greve et al, 2015;Xu et al, 2013;Yang et al, 2008;Donohue et al, 2012;Zhang et al, 2004;Knighton et al, 2020;Gao et al, 2020;Wu et al, 2019;Qiu et al, 2019;Liu et al, 2019b;Guo et al, 2019).…”
Section: Current Interpretations Of Explicit Budyko Curves and The Pamentioning
confidence: 99%
See 1 more Smart Citation
“…EI and DI corresponding to each sub-basin) should follow the theoretical Budyko curve (Creed et al, 2014). Any deviation of EI and DI from the theoretical Budyko curve suggest a change in the hydro-climatology of the river subbasin, one reason behind this could be climate change (Liu et al, 2019). Sinha et al (2018) applied Budyko framework to assess the impact of climate variability and anthropogenic activities on hydrologic resilience in Peninsular India and found that many subbasins of the Southern India were not enough resilient.…”
Section: Introductionmentioning
confidence: 99%